ANALISIS KINERJA WAITERS DI RESTORAN CAKRAWALA HOTEL ARYADUTA MANADO PADA ERA NEW NORMAL - Maliangkay, Julio Daniel; Bawole, Merry Theovanny; Warokka, Margaretha N (PolimdoSains, 2024)
The Covid-19 pandemic that occurred in 2019 in Indonesia has had an impact and changes in the restaurant industry in the hotel world, as well as the Cakrawala Restaurant at the Aryaduta Hotel Manado. Changes that have occurred include changes to the SOP in serving guests and also a reduction in the number of waiters at the Cakrawala Restaurant at the Aryaduta Hotel Manado. This makes waiters have to work optimally, especially after the pandemic enters the new normal period, where everything is gradually recovering and the hotel business is starting to get busy again. For this reason, the author carries out research on analysis of waiter performance at the Cakrawala Restaurant at the Aryaduta Hotel Manado during the new normal period. The research method used in this research is a descriptive qualitative research method. The research location, namely Cakrawala Restaurant Hotel Aryaduta Manado, was carried out during the months of 4 July 2022 to 4 January 2023. It is known that the Cakrawala Restaurant Hotel Aryaduta Manado has 3 waiters in charge of providing service since the pandemic and during the new normal period the number of waiters remains the same, namely 3 people working in 2 shifts. For this reason, waiters at the Horizon restaurant of the Aryaduta Hotel Manado are required to be able to work optimally by carrying out their duties and responsibilities in accordance with the existing SOPs, apart from that they must continue to work solidly and collaboratively in working with the team and routinely participate in every evaluation carried out. Apart from that, pay attention to factors that can influence the performance of waiters in improving the quality of their service, namely individual factors and management support factors, including: good mental attitude, education or training, work skills, good leadership and an appropriate income level.Keywords: Performance, waiters, Cakrawala restaurant